Exploring Community Perspectives on Household Waste Management in Dili: Insights from Lahane Oriental - De Carvalho Ximenes, Flora Martignonia; Roga, Anderias Umbu; Weraman , Pius (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2024)
This study explores the relationship between the knowledge, attitudes, and behavior of the community in managing household waste in the Urban Village of Lahane Oriental, Dili. This study was motivated by the growing global and local challenges of waste management, particularly in urban areas where population growth exacerbates this issue. This research employed an analytical observational design with a cross-sectional approach, using questionnaires distributed to 96 respondents selected through simple random sampling. Data were analyzed using descriptive statistics and Pearson’s correlation to assess the relationship between knowledge, attitudes, and behavior. The results showed that the majority of respondents (61.5%) had sufficient knowledge of waste management, while 62.5% demonstrated a positive attitude toward proper waste management. However, the community's waste management behavior did not fully meet the expected standards, despite generally positive attitudes and moderate knowledge. These findings indicate that, although knowledge and attitudes play an important role in influencing behavior, the lack of adequate infrastructure and institutional support remains a major obstacle to optimal waste management practices. It was concluded that further educational campaigns and improvements in waste management facilities are crucial for enhancing community engagement in sustainable waste management. The findings provide practical implications for local governments and policymakers in designing effective waste management interventions that consider both behavioral and structural factors.